Synthesis and Characterization of Microcrystalline Cellulose (MCC) from Corn Waste (Zea Mays L.) - Haliman, Annisa Cendani; Yuliati, Selastia; Hasan, Abu (UI Scholars Hub, 2025)
Corn (Zea Mays L.) is one of the most widely cultivated food crops in the world, including in Indonesia. Corn plants produce waste, especially husks and cobs. Corn waste has no economic value and can lead to environmental pollution if burned. Corn husks contain approximately 44.08% cellulose, while cobs have a cellulose content of 45%. This high cellulose content makes it possible to process corn waste into microcrystalline cellulose (MCC). This study aims to investigate the effect of NaOH concentration and delignification time on the characteristics of the resulting MCC products. A mixture of corn husk and cob was treated with NaOH solutions of 5%, 10%, and 15% concentration, for delignification periods of 30, 60, 90, and 120 minutes, respectively. Furthermore, 10% H2O2 was used in the bleaching process to obtain alpha cellulose, followed by hydrolysis using HCl 2.5 N. Characterization of the MCC products was executed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). The sample tests included organoleptic evaluations for shape, colour, and odour, as well as determination of the yield percentage, acidity, and moisture content. The crystallinity of the MCC obtained was satisfactory, while the SEM results indicated a pattern similar to Avicel pH 102. Increasing the concentration of NaOH resulted in smaller MCC particle sizes, facilitating dispersion during the acid hydrolysis. The NaOH concentration and delignification duration affected the yield percentage and surface contour, as observed in the SEM test, but the physical properties of the MCC were not affected by the concentration of NaOH. A concentration of 5% NaOH and a 90-minute delignification process yielded the highest crystallinity, at 99.4%, supported by a yield percentage of 77.09%, a pH of 5.84, a moisture content of 5.81%, and a particle size of 210.82 μm.